2017
DOI: 10.3389/fcimb.2017.00330
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Esx Factors Control Human Dendritic Cell Functions Conditioning Th1/Th17 Response

Abstract: The opportunistic pathogen Staphylococcus aureus (S. aureus) is a major cause of nosocomial- and community-acquired infections. In addition, many antibiotic-resistant strains are emerging worldwide, thus, there is an urgent unmet need to pinpoint novel therapeutic and prophylactic strategies. In the present study, we characterized the impact of infection with the pandemic methicillin-resistant USA300 S. aureus strain on human primary dendritic cells (DC), key initiators and regulators of immune responses. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 51 publications
1
23
0
3
Order By: Relevance
“…Although the capacity of DCs to kill the internalized staphylococci was limited, we did not observe any intracellular net growth of the bacteria. In line with our findings, previous studies demonstrated that human DCs have a low efficiency of killing internalized pathogens, especially when compared to human monocytes and macrophages [73][74][75]. This result is in agreement with the main function of DCs, which is to sense and process pathogens and present their antigens to T cells, rather than to eliminate all pathogens.…”
Section: Discussionsupporting
confidence: 93%
“…Although the capacity of DCs to kill the internalized staphylococci was limited, we did not observe any intracellular net growth of the bacteria. In line with our findings, previous studies demonstrated that human DCs have a low efficiency of killing internalized pathogens, especially when compared to human monocytes and macrophages [73][74][75]. This result is in agreement with the main function of DCs, which is to sense and process pathogens and present their antigens to T cells, rather than to eliminate all pathogens.…”
Section: Discussionsupporting
confidence: 93%
“…Targeting of flotillin scaffold activity could be an appropriate strategy for fighting bacterial infection by perturbing oligomerization of multiple virulence-related protein complexes such as T7SS. In mice, the T7SS Esx substrates participate in formation of persistent abscesses, probably due to the virulence of EsxA, EsxB, EsxC and EsxD secreted proteins [ 31 , 32 , 37 , 38 , 66 ]. In addition, EsxC is an immunogenic substrate, and kidney abscesses are associated with the generation of anti-EsxC antibodies [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, S. aureus mutants lacking the entire T7SS 7 or specific T7SS components (EsxA, EssB, EssC, EsxC, EsxB, EsaB, EsaD or EsaE) were consistently shown to be less virulent and/or persistent in various mouse infection models 11 , 17 21 . EsxA is necessary to delay apoptosis of S. aureus -infected epithelial and dendritic cells, while other substrates modulate cytokine production 18 , 22 , 23 . Although the relevance of T7SS to S. aureus is less understood, a role for the toxin-antitoxin pair EsaD (or EssD) and EsaG (or EssI) was recently demonstrated in intraspecies competition 9 , 15 .…”
Section: Introductionmentioning
confidence: 99%